PERFORMANCE ASSESSMENT OF ISLAMIC BANKS IN THE LEADERSHIP VALUE OF THE PROPHET MUHAMMAD: A CONCEPTUAL FRAMEWORK - Muhammad Yasir Nasution; Saparuddin Siregar; Syafrida Hani (Journal of Islamic, Social, Economics and Development, 2020)
This paper aims to describe a conceptual framework that will be used as an alternative assessment of the performance of Islamic banks. Motivated from the review of the literature conducted, researchers found so many statements from research results which revealed that the performance assessment used by Islamic banks is still dominated to financial goals, especially in profitability and financial health by financial aspects and not by Islamic values. The operational concept of Islamic bank is different from a conventional bank, but in its application, especially in Indonesia, the performance assessment instruments used in assessing the performance of a Sharia bank are not much different from the performance assessment of a conventional bank. Performance assessment for financial institutions in Indonesia, both banks and non-banks, is regulated by Bank Indonesia through the Otoritas Jasa Perbankan (OJK). Based on the data analysis of the results of a literature review that has been done, the researcher will compile a design model of Islamic banking performance assessment based on the characteristics of the leadership of the Prophet, namely the value of shiddiq, tabligh, Amanah, and fathanah. The design of this model is still in the form of a conceptual framework, using the author's grounded theory will make it the basis for further research.